Revisiting the design of selection systems in light of new findings regarding the validity of widely used predictors - SACKETT, Paul R. (Institutional Knowledge at Singapore Management University, 2023)
Sackett et al. (2022) identified previously unnoticed flaws in the way range restriction corrections have been applied in prior meta-analyses of personnel selection tools. They offered revised estimates of operational validity, which are often quite different from the prior estimates. The present paper attempts to draw out the applied implications of that work. We aim to a) present a conceptual overview of the critique of prior approaches to correction, b) outline the implications of this new perspective for the relative validity of different predictors and for the tradeoff between validity and diversity in selection system design, c) highlight the need to attend to variability in meta-analytic validity estimates, rather than just the mean, d) summarize reactions encountered to date to Sackett et al., and e) offer a series of recommendations regarding how to go about correcting validity estimates for unreliability in the criterion and for range restriction in applied work.